To ban or not ban political parties:correlates of turmoil and the problem of "Deutschian Conflict" in black Africa - Zakaria Haji Ahmad (Universiti Kebangsaan Malaysia, 1979)
Using a 32-nation sample from Black Africa, a test is made of Deutsch's hypothesis that primordial intergroup conflict is caused by social mobilization when social assimilation lags. A two-stage regression analysis is used to test the hypothesis. Both in terms of bivariate and multivariate regression analysis, it was discovered that indicators of low social assimilation are insignificant to explain primordial inter-group conflict; instead, it was found that the banning of political parties is statistically significant to the correlation. Simply therefore, conflict in SubSahara Africa is really political and bears little relationship to questions of ethnicity and primordialism. However, given the preliminary nature of the data and problems of data accuracy, the results must be regarded as only tentative.